The Influence of Critical Thinking, Learning Awareness, and the Effectiveness of AI Utilization on the Development of Independent Learning - Nabillah, Salsa; Fadliyah, Chairati; Abror, Abror; Zulafdal, Zulafdal; Friyatmi, Friyatmi (Universitas Negeri Makassar, 2025)
This study examines the Influence of Critical Thinking, Learning Awareness, and Effective Use of Artificial Intelligence (AI) on the Development of Independent Learning (SDL). Using the PRISMA-based Systematic Literature Review (SLR) approach, this study analyzes how these three variables interact to facilitate independent learning in the digital era. The analysis of the results shows that the development of SDL is greatly influenced by Critical Thinking skills that increase students' ability to analyze and analyze information, while Learning Awareness supports a deeper understanding of the learning process itself. The effective use of AI can accelerate the learning process by providing quick feedback and assisting students in designing learning paths that suit their needs. This finding stresses the importance of integrating these three variables to create a learning environment that supports the development of SDL. This study offers a conceptual framework that can be used to reflect on the effectiveness of using AI in supporting independent learning in the future